2017
DOI: 10.5194/bg-14-767-2017
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic composition of nitrate and particulate organic matter in a pristine dam reservoir of western India: implications for biogeochemical processes

Abstract: Abstract. Isotopic composition of nitrate (δ 15 N and δ 18 O) and particulate organic matter (POM; δ 15 N and δ 13 C) were measured in the Tillari Reservoir, located at the foothills of the Western Ghats, Maharashtra, western India. The reservoir, which is stratified during spring-summer and autumn seasons but gets vertically mixed during the southwest monsoon (SWM) and winter, is characterized by diverse redox nitrogen transformations in space and time. The δ 15 N and δ 18 O values of nitrate were low (δ 15 N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 55 publications
1
3
1
Order By: Relevance
“…We found strong seasonality in fortnight surface turbidity data at Rajghat, with high turbid (up to 400 NTU) water mostly occur between June and October. Our observations are confirmed by Bardhan et al [5], who reported significantly lower productivity during the monsoon period due to light-limited conditions in the Tillari reservoir of the Western Ghats region. Despite more significant nutrient loading, higher suspended sediment concentrations during monsoon season reduce light penetration.…”
Section: Biological Consumption and Change In Nutrient Ratiosupporting
confidence: 92%
See 3 more Smart Citations
“…We found strong seasonality in fortnight surface turbidity data at Rajghat, with high turbid (up to 400 NTU) water mostly occur between June and October. Our observations are confirmed by Bardhan et al [5], who reported significantly lower productivity during the monsoon period due to light-limited conditions in the Tillari reservoir of the Western Ghats region. Despite more significant nutrient loading, higher suspended sediment concentrations during monsoon season reduce light penetration.…”
Section: Biological Consumption and Change In Nutrient Ratiosupporting
confidence: 92%
“…Therefore, any large-scale turbulent mixing of reservoir waters and/or air-water interface is unlikely, restricting the loading of fresh oxygen to the anoxic water column. Bardhan et al [5] observed that the water column of 50 m deep Tillari reservoir remains thermally stratified during spring and summer months until the onset of monsoon. Greater reservoir depths, rapid settling of particles, and morphometry may not allow any intense wind-induced mixing and restricts the recycling of P. With changing physiochemical conditions in the reservoir, an additional amount of P may come from dissolution and desorption of P attached with sediment particles and onto the clay minerals.…”
Section: Biological Consumption and Change In Nutrient Ratiomentioning
confidence: 99%
See 2 more Smart Citations
“…At the other end of the spectrum, the positive offsets between δ 15 N‐DIN and δ 15 N‐ON in MRE and BRE suggest that N availability exceeded assimilatory demand. This contrasts findings from degraded temperate estuaries with small DON (< 50% TDN) pools (Ye et al ; Bardhan et al ). In BRE, these divergent ON vs. DIN patterns indicate that any NO 3 − or NH 4 + produced during the nitrification and mineralization promoted in other high‐turbidity estuaries (Damashek et al ) is not reassimilated into the biomass, creating the strong apparent fractionation between the PN and DIN pools.…”
Section: Discussioncontrasting
confidence: 75%